Hubungan antara Pengetahuan Ibu dengan Pemberian ASI Eksklusif pada bayi usia 6-12 bulan di wilayah kerja Puskesmas Tinoor Kecamatan Tomohon Utara - Astried Carolina Mathindas; Yulianty Sanggelorang; Ester Musa (Sam Ratulangi University, 2022)
Nutritional status is a sign of achieving the fulfillment of children's nutrition. One of the efforts to further develop children's nutrition is to give breast milk (ASI). The percentage of exclusive breastfeeding in Indonesia is still low, not reaching the national target of 80%. Knowledge is one element that can affect breastfeeding. The purpose of this study was to determine the relationship between mother's knowledge and exclusive breastfeeding for infants aged 6-12 months in the working area of Tinoor Health Center, North Tomohon Subdistrict, using an analytical design research method using a cross sectional methodology. The population in this study were all mothers who had babies 6-12 months old in the working area of the Tinoor Health Center, North Tomohon District in August-September 2021, totaling 74 people. The sample uses total sampling. The research instrument used a questionnaire in the form of a google form. Characteristics of respondents, most of them graduated from high school, namely 65 people (87.8%), and work as IRT were 64 people (86.5%), most of the respondents had moderate knowledge, 56 people (75.7%). Respondents who gave exclusive breastfeeding amounted to 53 people (71.6%). The results showed that there was no significant relationship between mother's knowledge and exclusive breastfeeding (p = 0.374). In addition to knowledge, exclusive breastfeeding can be influenced by several variables, including: occupation, age, habits, and health services. Therefore, information from television, articles and radio can provide knowledge to mothers, but not always be able to change the habits and behavior of mothers.